The role of short-term immigration on disease dynamics: An SIR model with age-structure - Sánchez, Fabio (2019)
We formulate an age-structured nonlinear partial differential equation model that features short-term immigration effects in a population. Individuals can immigrate into the population as any of the three stages in the model: susceptible, infected or recovered. Global stability of the immigration-free and infection-free equilibria is discussed. A generalized numerical framework is established and specific short-term immigration scenarios are explored.